2015
DOI: 10.1136/bmjqs-2014-003816
|View full text |Cite
|
Sign up to set email alerts
|

Characterising ‘near miss’ events in complex laparoscopic surgery through video analysis

Abstract: BackgroundRoot cause analyses of surgical complications are of high importance to ensure surgical quality, but specific details on technical causes often remain unclear. Identifying subclinical intraoperative incidents attributable to technical errors is essential for developing rescue mechanisms to prevent adverse outcomes.ObjectiveDescriptive study to characterise intraoperative technical error-event patterns in successful laparoscopic procedures.MethodsEvents (injuries) identified during prior blinded analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 28 publications
0
51
0
1
Order By: Relevance
“…Current initiatives to improve patient safety in surgery with an emphasis on system approaches, such as optimal antibiotic or heparin use, have had a minimal impact on surgical outcomes 2. However, it has been shown that peer video ratings of surgical skill strongly correlated with improved patient outcomes 3. Consequently, there has been growing interest in focusing on the operation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Current initiatives to improve patient safety in surgery with an emphasis on system approaches, such as optimal antibiotic or heparin use, have had a minimal impact on surgical outcomes 2. However, it has been shown that peer video ratings of surgical skill strongly correlated with improved patient outcomes 3. Consequently, there has been growing interest in focusing on the operation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Het is een uitdaging om een simpel, kosteneffectief en valide meetinstrument te ontwikkelen, dat tegemoet zal komen aan deze eisen van de overheid, patiëntengroepen, maar ook aan de eisen van professionals zelf. In de toekomst zou videoanalyse daarin mogelijk nog een belangrijke rol kunnen gaan spelen [10]. De ultieme doelstelling blijft: de kwaliteit van het medisch specialistisch handelen steeds verder optimaliseren en de patiëntveiligheid verbeteren.…”
Section: Toetsen Van Kennis En Kundeunclassified
“…Bonrath et al 4 add to our scientific understanding of intraoperative surgeon performance. The investigators reviewed 54 unedited videos of successful (uncomplicated) laparoscopic bariatric procedures to identify near-miss events using the Generic Error Rating Tool (GERT).…”
mentioning
confidence: 99%